Long-term effect of nutritional counselling on desired gain in body mass and lean body mass in elite athletes - Garthe, I.; Raastad, T.; Sundgot-Borgen, J. (Applied Physiology, Nutrition, and Metabolism, 2011)
Lean body mass (LBM) is important in power-related sports. In athletes with heavy training loads and competitions, it may be difficult to increase and maintain LBM during the season. The purpose of this study was to evaluate the long-term effects on body composition after an 8-12 week weight-gain period with or without nutritional guidance. Twenty-one elite athletes where randomized to 1 of 2 groups: the nutritional counselling group (NCG; n = 12, 18.5 ± 1.7 y, 67.8 ± 7.4 kg) and the ad libitum group (ALG; n = 9, 19.6 ± 2.7 y, 74.2 ± 5.7 kg). The NCG followed a meal plan that provided a surplus of 506 ± 84 kcal/day, whereas the ALG had an ad libitum energy intake (EI) during the strength-training (4 sessions per week) intervention. Body mass (BM) and body composition were measured pre- and postintervention, and 6 and 12 months after the intervention. EI in the NCG was normalized after 12 months, whereas EI in the ALG was unchanged during or after the intervention. BM increased more in the NCG than in the ALG during the intervention (4.3% ± 0.9% vs. 1.0% ± 0.6%) and after 12 months (6.0% ± 0.9% vs. 1.8% ± 0.7%). LBM increased in the NCG during the intervention (2.8% ± 0.5%) and after 12 months (4.4% ± 1.0%), whereas LBM in the ALG was unchanged. The NCG managed to maintain and increase BM and LBM after the intervention period. Hence, the focus on nutritional guidance, in addition to strength training, seems to be preferable for obtaining the long-term effect of weight gain in athletes.